Experimental and numerical studies of titanium foil/steel explosively welded clad plate - Zhi-xiong Bi; Xue-jiao Li; Ke Yang; Rong Kai; Quan Wang; Meng-ben Xu; Ting-zhao Zhang; Xian-de Dai; Jing-ye Qian; Yong Wu (Defence Technology, 2023)
Ti/Fe clad plate had attracted extensive attention because of its important application. In order to reduce the titanium layer thickness, the explosive welding of TA1 titanium foil to Q235 steel plate was carried out. The interfacial bonding performance was analyzed by micromorphology analysis and mechanical property test, and the formation process of interfacial wave and molten block in the vortex was simulated by smoothed particle hydrodynamics (SPH) method. The results showed that salt as pressure transfer layer used in explosive welding could play a good buffer effect on the collision between flyer and base layers. Regular waveforms were formed on the bonding interface, and the titanium foil/steel clad plate exhibited good welding quality and bonding property. The crest of the observed interfacial wave moved 200 μm from the beginning to the final formation, and it was important of jet on the formation of interfacial waveform. The interface was mainly bonded in the form of molten layer, and the grains near the interface were streamlined. Molten block containing intermetallic compounds and metal oxides appeared in the vortex of wave crest.